Proceedings of 1994 3rd International Conference on Software Reuse
DOI: 10.1109/icsr.1994.365803
|View full text |Cite
|
Sign up to set email alerts
|

Measuring software reusability

Abstract: This paper cxamines various approaches to measuring st,/ihiare reusability. Knowing what makes software "reusable" can help us learn how to build new reusable components and help US to identify potentially useful modules in existing programs. The paper begins by establishing a taxonomy of approaches to reusability metrics based on their empirical or qualitative orientation. The paper then examines the disciplines, theories, and techniques used by numerous existing reusability measurernent niethods as they rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
3

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 24 publications
(10 reference statements)
2
58
0
3
Order By: Relevance
“…Portability metrics measures the ability to transfer software from one system to another and is based on analyzing modularity and hardware/software context independence [14]. Learning objects portability can be measured as the context dependence at technological and socio-educational levels.…”
Section: Portabilitymentioning
confidence: 99%
“…Portability metrics measures the ability to transfer software from one system to another and is based on analyzing modularity and hardware/software context independence [14]. Learning objects portability can be measured as the context dependence at technological and socio-educational levels.…”
Section: Portabilitymentioning
confidence: 99%
“…If the integration affects more than one product from the 3 As for Hypothesis 2, the assumption is made that the available set of resources is kept constant. On the other hand, the initial effort for integration may be higher in the product line case due to some higher complexity of the product line infrastructure.…”
Section: Explanationmentioning
confidence: 99%
“…At the moment we can only hypothesize the form of the quantitative relationship (cf. [1,3,4,5]); we urgently need to perform experiments and gather data to confirm or reject our hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…In theory, reuse can lower development cost, increase productivity, improve maintainability, boost quality, reduce risk, shorten life cycle time, lower training costs, and achieve better software interoperability [1,2]. However, in practice, studies have shown that reuse is not always the best choice: it may be hard to implement, and the benefits of reuse cannot be reliably quantified [1].…”
Section: Introductionmentioning
confidence: 99%